Strengthen sheep and goat community-based breeding programs in Ethiopia towards scaling - Getachew, Tesfaye; Belay, Berhanu; Rekik, Mourad; Rischkowsky, Barbara; Ambecho, Zelalem Abate; Goshmie, Shenkutie; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2022)
Sheep and goat community-based breeding programs (CBBPs) has been implemented in Ethiopia since 2009. Initiated by the ILRI-ICARDA-BOKU, the programs are currently overseen by the International Research Center for Agricultural Research in the Dry Areas (ICARDA), in collaboration with international and national partners. Numerous field excursions to CBBP sites were conducted in an effort to determine if the foundational elements of CBBPs are in place, to strengthen and optimize the current CBBPs, and to facilitate their scaling. The visit considered the Washera and Wollo sheep scaling (WaWo) initiative sites, Bonga, Arsi Bale, and Menz sheep, as well as Hararghe Highland and Konso goat CBBPs. During the visit, suggestions and recommendations were given to the relevant team and community. In order to support CBBP, numerous institutions got 26,000 ear tags with markers, 41 applicators, 12 burdizo for castration on non-selected males. 25 weighing scales, veterinary supplies, and medicines such antibiotics and anthelminthics as well as needles, syringes, and therapies for external parasites. Two comprehensive laboratories for low-cost reproductive technology have been established at the universities of Injibara and Haramaya. Nineteen tablets and digital database training were made available to the WaWo initiatives (Injibara, Bahir Dar, Debre Markos, Mekdela Amba University, Andasa and Debre Berhan Research Centers, and the Water and Land Resource Center) to help with data collection. The Washera sheep and Central Highland Goat breed development teams received trainings in reproductive technologies after the creation of two laboratories at Injibara and Haromaya Universities. This training included 18 experts. A total of 219 breeding rams were purchased this year and given to the WaWo initiative.